Analisis Penggunaan Aplikasi Shopeepay Terhadap Perilaku Konsumtif Mahasiswa Manajemen Universitas Labuhanbatu - Eva Fitria; Elvina; Pitryani (ARBITRASE: Journal of Economics and Accounting, 2022)
ShopeePay has become a new lifestyle among Shopee users, because it makes purchasing and payment transactions easier. The purpose of this study was to analyze the use of ShopeePay on the consumptive behavior of Labuhanbatu University Management students. This research is a qualitative descriptive study. This research was conducted from June 2022 to November 2022. The samples in this study were students of the Management study program, Faculty of Economics and Business, Labuhanbatu University, totaling 346 students. Data collection techniques were carried out using in-depth interviews and giving questionnaires to assess ShopeePay usage. Data analysis techniques are carried out by detecting student consumptive behavior in using ShopeePay. The data is given coding which is then narrated and interpreted in a qualitative description. The results of the study show that there are more female ShopeePay users (250 people) than men (96 people). ShopeePay users are aged 18 and 20 years from the 2022 and 2020 batches. Use of ShopeePay for less than 3 months in making online transactions